Effects of cooking temperature in repetitive cooking-chilling cycles on resistant starch content and quality characteristics of fish crackers - Mohd Nor, Mohd Zuhair; A. Talib, Rosnita; Mohd Adzahan, Noranizan; Chin, Nyuk Ling; Hashim, Kamaruddin (Universiti Putra Malaysia Press, 2015)
This work describes the effects of different cooking temperatures in repetitive cooking-chilling (RCC) process on resistant starch (RS) content in fish crackers prepared in a ratio of 1:1 fish to sago starch formulation. In this work, three sets of four RCC cycles were performed on fish crackers, in which each set was cooked at fixed temperatures of 100, 115 and 121°C, respectively. The chilling temperature was fixed at 4°C in all cases. Subjecting the fish crackers to a higher cooking temperature for up to 4 cycles of RCC can increase the RS content. However, quality degradation was observed in the characteristics of the fish crackers. During the first RCC cycle, cooking at a higher temperature had caused the crackers to crack and burst. Besides, defragmentation to the shape of the fish cracker gels was also observed during the first RCC cycle, coupled with softer texture and high moisture content. When the products were subjected to frying, their linear expansion decreased, the texture became harder and the colour turned darker. This work demonstrated that the application of higher cooking temperature up to 4 RCC cycles was able to enhance the RS content in the fish crackers, but it was less able to attain the product’s perfect shape. On the contrary, fish crackers that were exposed to lower cooking temperatures contained lower RS but with less shape damage.